MBCL-45. ROLE OF IRRADIATION IN RELAPSED MEDULLOBLASTOMA: A REPORT OF THE GERMAN MEDULLOBLASTOMA RELAPSE STUDIES. Issue 2 (22nd June 2018) - Tippelt, Stephan; Küter, Julia; Mikasch, Ruth; Siegler, Nele; Warmuth-Metz, Monika; Rutkowski, Stefan; Mynarek, Martin; von Hoff, Katja; Pietsch, Torsten; Pfister, Stefan M; Witt, Olaf; Kortmann, Rolf-Dieter; et al.
Abstract: BACKGROUND: In pediatric patients with medulloblastoma (MB) the 5-year-OS rate dependent on risk group is 35% to 90%. In unresectable or metastatic recurrence longterm prognosis is poor. Aim of this study was to evaluate the role of irradiation in relapsed MB patients registered in the German studies HIT-MED, HIT-REZ-97/-2005 and HIT-REZ-Registry between July 1997 and December 2016. METHODS: Data analyzed at relapse were age, gender, stage, primary/relapse therapy, and follow-up. Kaplan-Meier analysis and log rank test were used to estimate the PFS/OS after 1 st recurrence and (re)irradiation. RESULTS: 257 patients with recurrent/refractory MB [75 female/182 male, median age 11.0 years (0.8-37.9), median PFS after 1 st diagnosis 24.8 months (2.6-270.2), 81% metastatic disease at relapse] were included in this analysis. Median PFS and OS after first relapse were 12.3 months (95%CI: 9.4;15.2) and 23.8 months (95%CI: 19.3-28.3), the 5-year-PFS and 5-year-OS rate were 6.8%±1.7% and 19.3%±2.7%, respectively. The PFS and OS differed significantly between 4 different cohorts: patients (A) with 1 st irradiation at 1 st relapse (n=29), (B) with re-irradiation (n=54), (C) without re-irradiation at 1 st relapse (n=164), and (D) without irradiation at any time (10). The best 5-year-PFS and 5-year-OS rate were observed in cohort A with 20.1% ±7.8 and 34.2% ±9.3, respectively. Looking for different strata significant differences were seen in patients with metastatic disease. CONCLUSIONS: Radiotherapy at relapse can be used as salvage therapy in patients without primary irradiation. It can lead to prolonged PFS and OS especially in patients with metastatic disease. Supported by German Children's Cancer Foundation.